Malawi : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This report on the Observance of Standards and Codes data module provides a review of Malawi's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by the in-depth assessment of the quality of five macroeconomic datasets. With the exception of the fiscal sector, Malawi publishes statistics for most of the comprehensive frameworks, data categories, and indicators recommended in the GDDS. The legal and institutional framework for the production of the five macroeconomic datasets of all institutions responsible for collecting, processing, and disseminating macroeconomic statistics is broadly adequate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet